Asymptomatic cholelithiasis in bariatric practice - Vladimir R. Stankevich; Alexander V. Smirnov; Alexandr I. Zlobin; Dmitry N. Panchenkov; Valentin I. Sharobaro; Yury V. Ivanov (Клиническая практика, 2023)
Background: The need for simultaneous cholecystectomy for asymptomatic cholelithiasis in patients undergoing bariatric intervention has not been proven. The experience of managing patients with obesity and concomitant disease cholelithiasis is presented.